2019
DOI: 10.3168/jds.2018-15281
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the origins of extant casein variation in goats

Abstract: The variation in the casein genes has a major impact on the milk composition of goats. Even though many casein polymorphisms have been identified so far, we do not know yet whether they are evolutionarily ancient (i.e., they existed before domestication) or young (i.e., they emerged after domestication). Herewith, we identified casein polymorphisms in a data set of 106 caprine whole-genome sequences corresponding to bezoars (Capra aegagrus, the ancestor of domestic goats) and 4 domestic goat (Capra hircus) pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
(95 reference statements)
2
7
0
Order By: Relevance
“…The π-values of each casein gene were estimated with VCFtools (Danecek et al 2011) as previously explained (Table S7). The π estimates obtained in the per-site analysis were consistent with those previously reported by Guan et al (2019) in goats and bezoars. Moreover, we observed higher π-values in the sheep CSN1S1, CSN1S2 and CSN3 genes when compared to those of mouflons.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The π-values of each casein gene were estimated with VCFtools (Danecek et al 2011) as previously explained (Table S7). The π estimates obtained in the per-site analysis were consistent with those previously reported by Guan et al (2019) in goats and bezoars. Moreover, we observed higher π-values in the sheep CSN1S1, CSN1S2 and CSN3 genes when compared to those of mouflons.…”
supporting
confidence: 89%
“…The comparison of casein variation between sheep and mouflons revealed an extensive sharing of polymorphic sites (Figs, 2C and S9), a finding that agrees well with results reported by Guan et al (2019) in goats and bezoars. Consistently, Chessa et al (2017) showed the existence of a haplotype formed by 8 SNPs that segregates in 51% of the mouflons as well as in the majority of the domestic sheep breeds sampled in their study.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…These genes have been characterized at the genomic [ 7 ], transcriptomic [ 8 ], and proteomic [ 9 ] levels. Furthermore, genetic polymorphisms and variants in casein genes have been reported in various animal species [ 10 ], including cattle [ 11 , 12 , 13 ], goats [ 14 ], and sheep [ 15 ], with goats and cows having the largest genetic variability. The identified variants have been associated with differential gene expression and rates of protein synthesis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…During breeding, casein genes acquired many sequence variations that can lead to altered gene expression and are characteristic of some goat and cow breeds (Yue et al, 2011;Fomichev et al, 2012;Guan et al, 2019). Many of these sequence variants could be used as markers for breeding.…”
Section: Introductionmentioning
confidence: 99%